Use of the Grubbs test to study the homogeneity of a NaI(Tl) detector (Brazilian Journal of Radiation Sciences, 2021)
The NaI(Tl) detector is one of the most used in gamma ray spectrometry because it presents high counting efficiency for gamma rays in a wide range of energy. The crystal can have a lower efficiency that can be indicated by the effects of its aging by several factors such as: the reaction of sodium iodide with magnesium oxide, absorption of water vapor by crystal, and problems related to photomultiplier. In an experiment, several measures can be take and when a doubt exists between one of the measured values it is possible to use a statistical test. Grubbs test is designed to verify the presence of extreme values in sample observations. This paper presents a methodology that has the objective of evaluating the homogeneity of a NaI(Tl) scintillation detector using the Grubbs test to validated the crystal homogeneity. The study pre-established five differents locations in frontal area of detector where measurements were performed using a 137Cs standard source in order to calculate the standard deviation.